In support of urban adaptation: a participatory assessment process for secondary cities in Vietnam and Bangladesh - Rahman, Mohammad Aminur; McEvoy, Darryn; Ahmed, Iftekhar; Trundle, Alexei; Sang, Le Thanh; Diem, Nguyen Ngoc; Suu, Lam Thi Thu; Quoc, Tran Ba; Mallick, Fuad Hassan; Rahman, Rezaur; Mukherjee, Nandan; Nishat, Ainun (© 1996 Taylor & Francis Online, 2016)
This article was published in the Climate and Development journal [© 2014 Taylor & Francis Online] and the definite version is available at : http://dx.doi.org/10.1080/17565529.2014.886991 The article website is at: http://www.tandfonline.com/doi/full/10.1080/17565529.2014.886991